Ibalizumab-Human CD4 Receptor Interaction: Computational Alanine Scanning Molecular Dynamics Studies - Su, Zhi-Yuan (Current Computer - Aided Drug Design, 2014)
Antibody drugs are used in the treatment of many chronic diseases. Recently, however, patients and doctors have encountered problems with drug resistance, and improving the affinity of antibody drugs has therefore become a pressing issue. Ibalizumab is a humanized monoclonal antibody that binds human CD4, the primary receptor for human immunodeficiency virus type 1 (HIV-1). In this study, we sought to identify the key residues of the complementaritydetermining regions (CDRs) of ibalizumab. Virtual alanine mutations (complementarity-determining regions of ibalizumab) were also studied using solvated interaction energies derived from molecular dynamics and the explicit water model. Using 1,000 nanosecond molecular dynamic simulations, we identified six residues: Tyr50 [HCDR2], Tyr53 [HCDR3], Asp58 [HCDR2], Glu95 [HCDR2], and Arg95 [LCDR3]. The Robetta alanine-scanning mutagenesis method and crystallographic information were used to verify our simulations. Our simulated binding affinity of −17.33 kcal/mol is close to the experimentally determined value of −16.48 kcal/mol. Our findings may be useful for protein engineering the structure of the ibalizumab-human CD4 receptor complex. Moreover, the six residues that we identified may play a significant role in the development of bioactive antibody analogues.
Keywords: human immunodeficiency virus type 1 (HIV-1)